Призрак кошки: для среднего школьного возраста / Холли Вебб - Вебб Холли (Мейзи Хитчинс, 2017)
Экземпляры: ф.8 (20170913) / Инвентарный номер: 57485 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: В 26 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)-44